PENGEMBANGAN KURIKULUM PENDIDIKAN BERBASIS MULTIKULTURAL: TEORI DAN PRAKTIK - Arif Muzayin Shofwan (STAI Darul Qalam Tangerang, 2025)
Curriculum development in education must be carried out with various considerations. This qualitative descriptive study, using a literature review, discusses the development of a multicultural-based curriculum from both theoretical and practical perspectives. The data were analyzed using content analysis, selecting data that aligns with the research focus. This paper concludes that a multicultural-based education curriculum is one that embraces cultural diversity and consistently explores differences as a divine necessity. Multicultural-based curriculum development aims to respect all diversity, create peace, protect human rights, and foster democracy. Several learning developments that teachers should focus on for students in a multicultural-based curriculum include: peace learning, human rights learning, and democracy learning. Furthermore, if multicultural-based curriculum development is linked to Islamic religious education, it must be grounded in psychological, sociological, and philosophical foundations, and adhere to the principles of relevance, effectiveness, efficiency, and flexibility